2022
DOI: 10.3138/jsp-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Predatory Journals in Journalism and Mass Communication: A Case Study of Deceptions

Abstract: Predatory publishing is an increasingly difficult challenge to ignore because it threatens the integrity of research literature and scholarship. Still, this scholarly area is largely overlooked in journalism and media communications (J&MC) literature. This case study examines two J&MC journals from companies listed as possibly predatory by analyzing the experiences of scholars purportedly affiliated with them. Using a survey and interviews, the analysis suggests that these journals used deceptive and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…That aside, 22 of the stock or other academic characters in this report have not only amassed a small or large number of editorial board memberships that have evidently not disadvantaged them in the course of their careers, despite the fact that those memberships should really be a personal and institutional embarrassment, they have also benefited, or at least remained unharmed, by publications in the worthless journals concerned. This matter has been mentioned in numerous contexts (Frandsen et al, 2022; Freedman & Kurambayev, 2022; Kolata, 2017; Pyne, 2017; Wang et al, 2023), but always anonymously and statistically, never critically and personally (e.g., Nejadghanbar et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…That aside, 22 of the stock or other academic characters in this report have not only amassed a small or large number of editorial board memberships that have evidently not disadvantaged them in the course of their careers, despite the fact that those memberships should really be a personal and institutional embarrassment, they have also benefited, or at least remained unharmed, by publications in the worthless journals concerned. This matter has been mentioned in numerous contexts (Frandsen et al, 2022; Freedman & Kurambayev, 2022; Kolata, 2017; Pyne, 2017; Wang et al, 2023), but always anonymously and statistically, never critically and personally (e.g., Nejadghanbar et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The Issue with Editorial and Publication StandardsResearch have shown that predatory journals lack the required standards and best practices. These standards and practices include publishing corrections and retractions as needed, processes to deal with alleged research misconduct (to ensure allegations of research misconduct are appropriately addressed), screening for plagiarized content, re-viewing ethics of research conduct, requiring authorship statements to attempt to exclude ghost and guest authors, and requiring funding and conflicts of interest disclosures[18].In this section of the study, the researchers reviewed several relevant research articles that are linked to this research inquiry conducted on predatory journal publication and ethical principles associated with journal publication. The following represents a summary from the articles reviewed and possible suggestions were put together according to[19].…”
mentioning
confidence: 99%